Plasmodium falciparum Homologue of the Genes for Plasmodium vivax and Plasmodium yoelii Adhesive Proteins, Which Is Transcribed but Not Translated - Taylor, Helen M. (American Society for Microbiology, 2001)
The 235-kDa family of rhoptry proteins in Plasmodium yoelii and the two reticulocyte binding proteins of P. vivax comprise a family of proteins involved in host cell selection and erythrocyte invasion. Here we described a member of the gene family found in P. falciparum (PfRH3) that is transcribed in its entirety, under stage-specific control, with correct splicing of the intron, but appears not to be translated, probably due to two reading frameshifts at the 5′ end of the gene.